Many‐Body Dispersion Interactions in Molecular Crystal Polymorphism1. Issue 26 (16th May 2013) - Marom, Noa; DiStasio, Robert A.; Atalla, Viktor; Levchenko, Sergey; Reilly, Anthony M.; Chelikowsky, James R.; Leiserowitz, Leslie; Tkatchenko, Alexandre
<x xml:space="preserve">Abstract</x> Molecular crystals: The structures and relative energies of glycine polymorphs are determined using dispersion corrections to PBE and PBEh density functionals. The picture shows a potential‐energy surface for the a‐b plane of γ‐glycine obtained with density functional theory including many‐body dispersion interactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>